Implementation of Conversational Artificial Intelligence in a3-Dimensional Game onWaste Impact - Faisal Reza Pradhana; Ilham Mufandi; Aziz Musthafa; Dian Afif Arifah; Khairul Munzilin Al Kahfi (Universitas Bumigora, 2025)
The escalating volume of waste in Indonesia presents significant environmental challenges, primarilydue to insufficient public awareness and engagement. This study aimed to develop a dynamic threedimensionalsimulation game to enhance young people’s understanding of the environmental impactsof waste. The game integrates conversational artificial intelligence technology to create non-playablecharacters that engage users in natural text and voice dialogues. The research employed a research anddevelopment approach following the Software Development Life Cycle waterfall method, encompassingstages of analysis, design, implementation, testing, and maintenance. The game design adopted theMechanical, Dynamic, and Aesthetic framework method. It implemented a first-person perspective tocreate an immersive learning experience: evaluation involved functionality tests, expert reviews, anduser trials. The functionality testing achieved a perfect score of 100 percent, while evaluations by educationaltechnology experts yielded an average score of 94 percent for content quality and interfacedesign. User trials, conducted with individuals aged 10 to 18, indicated a high level of satisfactionwith an average score of 86 percent. These results conclude and demonstrate that integrating conversationalartificial intelligence into a simulation game provides an engaging and effective educationaltool to raise environmental awareness. Nonetheless, the study highlights the need for ongoing supportfrom parents and educators to cultivate sustainable waste management practices among young people.Future research should focus on expanding the game’s scope and evaluating its long-term impact onusers’ environmental literacy.